Comparison of digital and conventional assessment methods for a single tooth preparation and educational satisfaction. (10th April 2022) - Kim, Yeong‐Kyu; Kim, Jae‐Hoon; Jeong, Yuwon; Yun, Mi‐Jung; Lee, Hyeonjong
Abstract: Introduction: Digital feedback for tooth preparation can provide dental practitioners with more objective and accurate evaluations compared to conventional methods. This study aimed to evaluate the educational effect and satisfaction of digital feedback compared with those of the conventional putty index method for tooth preparation. Material and Methods: Forty‐eight third‐grade dental students were selected. All students performed a full‐coverage preparation on a right mandibular first molar resin tooth. They were randomly divided into four groups ( n  = 12)—no guide (control), putty index, digital feedback, and digital and putty index assessment. Three‐dimensional analysis was performed using an analysis software (GomInspect 2018, Gom) to evaluate the amount of tooth structure removed. At the end of the practice, the students completed a questionnaire to evaluate the educational satisfaction of the respective methods. Results: There was no statistical significance of the amount of preparation amongst groups in most of the measured areas only except for several specific points. Overall occlusal surface showed 0.99 ± 0.27 mm in the N group (no guide) and 1.15 ± 0.31 mm in the D group (digital feedback), and overall axial surface showed no statistical differences ( p  > .05). The groups that used digital assessment showed a high level of satisfaction compared with conventional assessment. Conclusions: It was difficult to confirm that the digital‐based feedback promotes accurate tooth preparation compared to conventional feedback within the limitation of this study. However, it improved educational satisfaction and permitted objective evaluation.